THE NICKEL PARADOX: CSR LIMITATIONS AND SOCIAL-ECOLOGICAL DISRUPTIONS IN CENTRAL HALMAHERA - Abdullah Yusuf Muflih; Tafrikhul Khotir; Muhammad Adam Fathurrahman (UNIVERSITAS SEBELAS MARET (UNS), 2025)
Nickel downstreaming is considered a key step in boosting Indonesia's economic growth. However, nickel mining practices remain a serious issue, particularly in terms of their impact on local communities and the environment. Corporate Social Responsibility (CSR) aimed at balancing economic benefits with local and environmental sustainability is often seen as inadequately implemented by companies. This study examines the socio-ecological impacts of nickel mining at PT IWIP in Central Halmahera, focusing on the effects of CSR initiatives on local communities and the environment. Data were collected through in-depth interviews with local community members, government representatives, and NGOs, along with participatory observation. Thematic analysis was used to identify key themes from participants’ perspectives. The study found that while PT IWIP’s CSR programs improved infrastructure and social access, the benefits were unevenly distributed, with marginalized groups receiving limited support. Furthermore, ecological degradation from mining activities increased the vulnerability of local communities to natural disasters. This research contributes to the understanding of CSR in resource extraction industries, emphasizing the need for more inclusive and sustainable CSR practices to address socio-ecological risks. The study recommends PT IWIP revise its CSR strategy to focus on long-term sustainability and inclusive community development.